Evaluation of digital reference services among academic and research libraries in Metro Manila towards the development of digital reference service guidelines for the Philippines - Natividad, Karen Cecille V.; Obille, Kathleen Lourdes B.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
As the means of communication, socialization, business and other aspects of life continue to change because of the booming technologies and innovations, it is safe to say that the way people access and acquire information also change. From books to CD-ROMs to the Internet as the sources and from in-person to telephone to online as the medium. This has been one of the challenges of reference librarians, being where the clients are. Before, patrons go to the reference desk to inquire. But now, since there are also patrons who prefer to use technology in acquiring information, the reference librarian needs to make sure that she is also there to guide them. Thus, she needs to extend her presence in the online world without leaving her usual desk.
To make sure that librarians are creating a satisfying experience for the users, librarians need to follow guidelines and standards. IFLA and ALA have established guidelines for digital reference services. However, its applicability to the Philippines is in question. Also, it may not be an appropriate tool in assessing digital reference services in the Philippines. It is in this light that the paper aimed to (1) present the current practices of academic and research libraries in the Philippines which offer digital reference service in developing and implementing such services, (2) assess the digital reference services of the academic and research libraries in the Philippines, (3) present the user's attitude and satisfaction towards the digital reference services, (4) determine the required competencies of reference librarians in providing digital reference services as perceived by the users and librarians, (5) identify the perceived service behaviors that the reference librarians should possess in digital reference services, and (6) formulate a set digital reference services guidelines for academic and research libraries for the Philippines.
To compare variables in different groups, the study employed a cross sectional research design. Content analysis was done in order to assess transcripts and a five point Likert scale was used to measure user perspectives and attitudes. The study yielded the following major results: (1) preliminary research on the digital reference services as well as the service being offered in the area were not done by all libraries who are currently implementing digital reference services, (2) since answers given by librarians are expected to be accurate, this characteristic was the most prominent characteristic in both email and chat transcripts among other characteristics in assessing the quality of answers, (3) the set of competencies under "Commitment to lifelong learning" are strongly perceived by the users that reference librarians should possess while competencies under "Knowledge of policies, procedures, ethics and issues" are strongly perceived by librarians, and (4) users expect reference librarians to provide proper referrals behaviors whenever necessary. The same is true for librarian with the addition of proper listening/ inquiry behaviors for the librarians. Also, both users and librarians were not particular on how librarians address the users .
Thesis
Keywords: Academic libraries -- Philippines -- Metro Manila; Electronic reference services (Libraries).; Reference services (Libraries).